Wednesday

April 16, 2014

April 16, 2014

Posted by **Sab** on Tuesday, August 28, 2012 at 10:48am.

OK, I have started by rearranging the formula:

8n(r+s)=8s(r-s)

What do I do next?

- algebra -
**Reiny**, Tuesday, August 28, 2012 at 11:02amso you must have meant

(r+s)/(8s)=(r-s)/(8n)

so 8n(r+s)=8s(r-s) is correct so far. Le'ts expand it

8nr + 8rs = 8rs - 8s^2

8nr = -8s^2

nr = -s^2

r = -s^2/n

- algebra -
**Sab**, Tuesday, August 28, 2012 at 11:05amthank you!

- algebra -
**Sab**, Tuesday, August 28, 2012 at 11:10amjust realised, should the second line be

8nr+8NS?, not 8rs?

- algebra -
**Sab**, Tuesday, August 28, 2012 at 11:15amjust realised, should the second line be

8nr+8NS?, not 8rs?.........

- algebra -
**Reiny**, Tuesday, August 28, 2012 at 11:18amyour are right, good for you to notice

I have to mind my n, r and s's

8nr + 8ns = 8rs - 8s^2

collect all terms containing r to one side

8nr - 8rs = -8s^2 - 8ns

factor out the r

r(8n - 8s) = -8s^2 - 8ns

r = (-8s^2 - 8ns)/(8n - 8s)

divide top and bottom by 8 on the RS

r = (-s^2 - ns)/(n-s)

or -s(s+n)/(n-s)

- algebra -
**Sab**, Tuesday, August 28, 2012 at 11:23amgreat, that makes sense, thanks

**Related Questions**

algebra - Rearrange (r+s)/8s=(r-s)/8n to make r the subject. OK, I have started ...

Math - Hello.I need to rearrange the following to make b the subject' a = 10/b-z...

rearrange this equation - Rearrange to make f the subject, showing your work ...

alg - Which expression represents the sum of the following? (3n / n^2 - 2n + 1...

math - 2/27(x-3)√((x^2-6x+23)/y)rearrange the equation to make y the ...

math - 2 = 8 (s + 7) 2 = 8s + 56 56 - 2 = 8s 54 = 8s /8 /8 6.75 = s did i do ...

maths - i have fopur questions like this but don't undersand them. thanks ...

math - given that R= 2p(squared) divided by Q-3 1)Calculate the value of R when ...

math - how can i rearrange R=pl/A to make p the subject. thx Bronson.

maths - How do i rearrange the equation to make d the subject. e = d/ab (d/ab ...